2013
DOI: 10.2135/cropsci2013.03.0130
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in a Worldwide Collection of Sainfoin Using Morphological, Anatomical, and Molecular Markers

Abstract: Genetic information on sainfoin (Onobrychis viciifolia Scop.), an important forage species, is highly limited. In this study, genetic diversity and trait relationships of 80 sainfoin accessions were evaluated using morphological, anatomical, and inter‐simple sequence repeats (ISSR) characteristics. Results of 2 yr of study indicated a wide range of variability in the germplasm using all three data sets. Based on morphological assessment, accessions were divided into three different groups that could be easily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 48 publications
2
28
1
Order By: Relevance
“…This can facilitate selection of ecotypes with variable tolerance to drought stress. Similar patterns of association among geographical characteristics with days to flowering, plant height, number of shoots per plant, and palatability have been reported by Zarrabian et al (2013) in sainfoin. Kerman is one of the driest provinces in southeast Iran.…”
Section: Discussionsupporting
confidence: 80%
“…This can facilitate selection of ecotypes with variable tolerance to drought stress. Similar patterns of association among geographical characteristics with days to flowering, plant height, number of shoots per plant, and palatability have been reported by Zarrabian et al (2013) in sainfoin. Kerman is one of the driest provinces in southeast Iran.…”
Section: Discussionsupporting
confidence: 80%
“…However, this distinction may be the reflection of different domestication routes with different ancestors. Using morphological, anatomical, and ISSR traits on 80 accessions of O. viciifolia, Zarrabian et al (2013) showed that the high level of population differentiation may comply with the theoretical prediction from an "isolation by distance" model. In this model, total population is assumed to be divided into subgroups, each breeding at random within itself.…”
Section: Within Species Diversitymentioning
confidence: 68%
“…This genus contains various annual and perennial species that can be distinguished mostly by their morphology and geographical distribution extending from the western Himalayas to Caucasia, Eurasia, North America, and Africa (Pavlova and Monova, 2000). However, almost all the Onobrychis species are restricted to northwestern Asia, especially to Iran and Anatolia, making this area the specific home of this genus diversity (Yildiz et al, 1999;Zarrabian et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers used ISSR markers to study genetic diversity within and among populations of forage crops (Bolourchian et al, 2013;Jonaviclene et al, 2009;Zarrabian et al, 2013;Shirvani et al, 2013). Better reproducibility of products of ISSR bands compared to other markers such as RAPD could be due to its longer SSR-based primers with higher annealing temperatures (Huangfu et al, 2009).…”
Section: Genetic Diversitymentioning
confidence: 99%